Silver nanoparticle modified surfaces induce differentiation of mouse kidney-derived stem cells. Issue 36 (4th June 2018) - Roy Chowdhury, Neelika; Hopp, Isabel; Zilm, Peter; Murray, Patricia; Vasilev, Krasimir
Abstract : 2-Methyl-2-oxazoline plasma polymerized silver nanoparticles containing coatings are not toxic towards mouse kidney derived stem cells (mKSCs) and regulate mKSCs differentiation. Abstract : In this paper, we interrogate the influence of silver nanoparticle (AgNPs)-based model surfaces on mouse kidney-derived stem cells (mKSCs) differentiation. The widespread use of silver in biomedical and consumer products requires understanding of this element's effect on kidney cells. Moreover, the potential for using stem cells in drug discovery require methods to direct their differentiation to specialized cells. Hence, we generated coated model substrates containing different concentrations of surface immobilized AgNPs, and used them to evaluate properties and functions of mKSCs. Initially, mKSCs exhibited reduced viability on higher silver containing surfaces. However, longer culture periods assisted mKSCs to recover. Greater degree of cell spreading and arborization led by AgNPs, suggest podocyte differentiation. Proximal tubule cell marker's expression revealed differentiation to the specific lineage. Although the exact mechanism underpinning these findings require significant future efforts, this study demonstrate silver's capacity to stimulate mKSC differentiation, which may provide opportunities for drug screenings.